Ecological food production from animal origin in the dehesa agrosystem of Andalucia and Extremadura - Mata, C; Caballero, I; Labrador, J; Casco, J M G (BASIS OF THE QUALITY OF TYPICAL MEDITERRANEAN ANIMAL PRODUCTS, 1998)
Andalucia and Extremadura gather certain advantages and conditions for the development of ecological stockbreeding which place them among the European territories of greatest potential in this sense. There are wide areas of high environmental balance, some of them declared as Natural Protected Areas-, with soils of only forestal and silvopastoral use, and with a lot of farms used for the traditional extensive stockbreeding. In this area the management is close to the ecological stockbreeding, and the location coincides with the one of dehesa farms. Most of these farms suffer problems derived from the pressure to which they are subjected because of a management towards greater intensification. Their functions are not valued properly. Many times their products are not competitive with the usual market prices. Being, however of greater organoleptic, sanitary, environmental quality and being even greater, their possibility of profitability. The conversion of extensive stockbreeding farms into a type of ecological production may provide solutions to these problems, favouring a consolidated development; and at the same time, it may encourage an action integrated with other agrarian farms, producing sites of pluriactivity and much more profitability. This work shows a description of the most relevant aspects of extensive stockbreeding productions in relation to its conversion into the ecological production.
Keywords: animal ecological production; Dehesa